KESANTUNAN BERBAHASA PENGGUNA MEDIA SOSIAL INSTAGRAM: KAJIAN SOSIOPRAGMATIK - Fallianda Alibasyah (Department of Master of Linguistic, Universitas Airlangga, 2018)
In establishing social interaction, the consideration of face concept is able to show the system of linguistic politeness and the reflection of participants’ attitudes. The consideration of face concept is not only present in face-to-face interaction but also in the context of online interaction. This study uses social media platform Instagram, namely “infogresik”, as the main data source. The data collection was taken from the comments between the Instagram operator and other Instagram users. This study uses the qualitative approach to obtain descriptive explanation on the percentage of selecting particular strategies. Politeness theory and social variable by Brown and Levinson (1987) become the main reference in the data analisis process. The result of the data analysis showed that the participants used positive politeness with the percentage of 81.3%, the negative politeness strategy of 10.2%, the off-record strategy and bald on-record strategy of 7.6% and 3.4% respectively. Furthermore, the influence of social distance variables and the level of speech act mostly influence to the selection of face-saving stratgey for the Instagram users.